Microstructure-polarization relations in nickel/gadolinia-doped ceria anode for intermediate-temperature solid oxide fuel cells - Choi, Yun-Gyeom; Park, Jun-Young; Song, Huesup; Kim, Hae-Ryoung; Son, Ji-Won; Lee, Jong-Ho; Je, Hae-June; Kim, Byung-Kook; Lee, Hae-Weon; Yoon, Kyung Joong (ELSEVIER SCI LTD, 2013)
Intermediate-temperature solid oxide fuel cells (SOFCs) based on gadolinia-doped ceria (GDC) electrolyte were successfully fabricated. The cells were composed of Ni-GDC anode substrate, Ni-GDC anode functional layer, GDC electrolyte, (La0.8Sr0.2)CoO3 (LSC)-GDC cathode functional layer, and LSC cathode current collector. Anode substrates were fabricated by die compaction of granules prepared by spray drying process, and poly(methyl methacrylate) (PMMA) was employed as a pore former for rapid transport of reactant and product gases across the thick anode. The shape and the distribution of pores in the anode substrate were significantly affected by the properties of suspension in spray drying process, and a uniform and interconnected pore structure was obtained by increasing solids loading due to reduced phase separation. High solids loading also improved thermal compatibility between the anode and the electrolyte in a co-firing process, resulting in reduced micro-defects in the electrolyte. Substantial reduction of anode concentration polarization as well as increased open circuit voltage was measured in cell test, and the maximum power density of 550 mW cm(-2) was obtained with humidified H-2 as fuel and air as oxidant at 650 degrees C. (C) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: FLUE-GAS PURIFICATION; ELECTROCHEMICAL-CELLS; SOFC ANODE; PERFORMANCE; FABRICATION; DENSIFICATION; ELECTROLYTE; CERAMICS; CATHODES